2019
DOI: 10.15244/pjoes/95032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Artificially Polluted with Lead on an Invasive Fallopia x bohemica: A Case Study from Central Europe

Abstract: Pollution with heavy metals is one of the most noticeable environmental problems due to their adverse ecological effects reported by many publications [1-3]. Toxic metals contaminating the soils create difficult conditions for most plants growing in them. They may cause various morphological, physiological, and biochemical dysfunctions in plants, either directly or indirectly, and cause damaging effects [2]. Heavy metal toxicity in plants varies with plant species, specific metal, content of metal, its chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The greenhouse experiment procedure was conducted according to a study by Sołtysiak and Brej (2019), where the effect of different doses of Pb on invasive Fallopia x bohemica (a hybrid of F. japonica and F. sachalinensis) was examined. The prepared plant materials (rhizome fragments of F. japonica) were introduced into plastic pots (one rhizome in each pot) with a capacity of 5 kg of soil.…”
Section: Greenhouse Experiments Proceduresmentioning
confidence: 99%
“…The greenhouse experiment procedure was conducted according to a study by Sołtysiak and Brej (2019), where the effect of different doses of Pb on invasive Fallopia x bohemica (a hybrid of F. japonica and F. sachalinensis) was examined. The prepared plant materials (rhizome fragments of F. japonica) were introduced into plastic pots (one rhizome in each pot) with a capacity of 5 kg of soil.…”
Section: Greenhouse Experiments Proceduresmentioning
confidence: 99%
“…In some cases, plant morphology is not affected by the presence of higher levels of heavy metals. For example, there was no negative effect of even a high dose of Pb found on the morphological characteristics of a Fallopia x bohemica hybrid [66]. Moreover, plant height in Japanese Knotweed s.l.…”
Section: Morphological Plasticitymentioning
confidence: 94%
“…Preliminary field studies in the city of Wrocław, Poland, have shown that the increased content of heavy metals in the soil does not reduce the invasion of Reynoutria japonica, but on the contrary, it is competitive with other plant species (Sołtysiak et al 2014).…”
Section: Japanese Knotweed Reynoutria Japonica (Polygonaceae) Synonym...mentioning
confidence: 99%